A quebra de limites do mal moral em Michael Kohlhaas - Silva, Carina Zanelato (Universidade de São Paulo/Faculdade de Filosofia, Letras e Ciências Humanas/Programa de Pós-Graduação em Língua e Literatura Alemã, 2016)
Abstract Ricoeur (1988) tells us that the concept of evil is a problem that goes through the centuries, due to its need for logical consistency. Already discussed its origin, its causes and its effects, but never came to a term that would eliminate the contradiction at its core. In this space, the literary works of Heinrich von Kleist (1777-1811) present a theme that includes a break of boundaries between the concepts of evil and goodness developed during the Aufklärung, highlighting this problem. This break seems to be strongly associated with the relationship between the I and the chaotic world in which it is inserted, resulting in a complexity of the sources of moral evil that dilutes the boundaries between good and evil and lead us to challenge these tight limits. Therefore, we try to demonstrate in this paper what this boundary break is made of and how the composition of a reality guided by mistakes integrates Kleist's literary universe, especially in the work Michael Kohlhaas.

Resumo Ricoeur (1988) nos diz que a conceituação do mal é um problema que atravessa séculos, devido a sua necessidade de coerência lógica. Já se discutiu sua origem, suas causas e seus efeitos, porém nunca se chegou a um termo que eliminasse a contradição em seu cerne. Neste espaço, as obras literárias de Heinrich von Kleist (1777-1811) apresentam uma temática que abarca uma quebra de limites entre os conceitos de maldade e bondade desenvolvidos durante a Aufklärung, evidenciando essa problemática. Essa quebra nos parece estar fortemente associada à relação existente entre o eu e o mundo caótico em que este está inserido, implicando em uma complexidade das fontes do mal moral que diluem as barreiras entre bem e mal e nos levam à contestação destes limites estanques. Procuraremos, portanto, neste texto, demonstrar em que consiste essa quebra de limites e como a composição de uma realidade pautada no engano integra o universo literário kleistiano, principalmente na obra Michael Kohlhaas.
Breaking boundaries of moral evil in Michael Kohlhaas
Keywords: Heinrich von Kleist; moral evil; Michael Kohlhaas; Heinrich von Kleist; mal moral; Michael Kohlhaas